Infantile Hemangioma With Minimal or Arrested Growth (IHMAG): A Retrospective Analysis of Clinical and Dermoscopic Diagnostic Clues - Neri, Iria; Orioni, Gionathan; Leuzzi, Miriam; Facchini, Elena; Mengozzi, Elena; Chessa, Marco Adriano (Dermatology Practical & Conceptual, 2024)
Introduction: Infantile hemangioma with minimal or arrested growth (IHMAG) is an unusual subset of infantile hemangioma, difficult to recognize because they are often mistaken with capillary malformation or other entities. Dermoscopic features of IHMAG have been described only in small case series so far. Objectives: The aim of our study is to evaluate epidemiological, clinical and dermoscopic features in 79 cases of IHMAG with a specific focus on neonates and toddlers with segmental complicated IHMAG and to provide a remarkable dermoscopic criteria to achieve diagnosis. Methods: This case series collected all the cases of IHMAG recorded in our Clinical Registry from January 2012 to March 2022. Results: A total of 79 cases of IHMAG were identified in our study; 53 (67.1%) were localized and 26 (32.9 %) were segmental. Patients showed any complications during the follow up, as ulceration and soft tissue anomalies. One PHACE syndrome and 2 LUMBAR syndromes were included. Our study highlights the main dermoscopic features differentiating IHMAG from infantile hemangiomas and capillary malformations in neonatal patients, highlighting the presence of enlarged, unfocused telangiectatic vessels as remarkable clues. Conclusions: This is a large case series described in literature about this rare entity. We emphasize that segmental IHMAG may be associated with structural abnormalities and may pose a diagnostic challenge especially in its rare facial segmental localization. The use of dermoscopy has allowed us to find typical signs for IHMAG, thus avoiding the execution of invasive methods and ensuring a prompt suspect of a syndrome on segmental neonatal cases.